Effect of dietary intake of trimethylamine on human metabolism of the industrial catalyst dimethylethylamine. Issue 7 (July 1995) - Lundh, T; Akesson, B; Skerfving, S
Abstract : OBJECTIVES–The aim was to study the effect of trimethylamine (TMA) on the metabolism of the industrial catalyst dimethylethylamine (DMEA) to ascertain whether biological monitoring of industrial exposure to DMEA is compromised and excretion of the malodorous DMEA in sweat and urine is increased by dietary intake of TMA. METHODS–DMEA (0/25 mg) and TMA (0/300/600 mg) were given simultaneously once weekly for six weeks to five healthy volunteers. Plasma was collected before and one hour after the doses, and urine 0-2, 2-4, 4-6, 6-8, and 8-24 hours after the doses. Specimens were analysed by gas chromatography with a nitrogen sensitive detector. RESULTS–Both amines were readily absorbed from the gastrointestinal tract and excreted in urine within 24 hours (DMEA 80%; TMA 86%). Oral intake of TMA increased the DMEA content of plasma and urine dose dependently, although there were large individual differences. Plasma and urinary TMA concentrations also increased, but not dose dependently. Moreover, the findings suggested the formation of endogenous TMA, little dealkylation of DMEA and TMA, and considerable first-pass metabolism. CONCLUSIONS–Although intake of TMA reduced N-oxygenation of DMEA and TMA, total urinary DMEA values (aggregate of DMEA and its oxide DMEAO excretion) were unaffected. Thus, monitoring occupational exposure to DMEA by analysis of biological specimens is not confounded by dietary intake of TMA, provided that total urinary DMEA is monitored. Although the increased urinary and hidrotic excretion of DMEA may contribute to body odour problems, they were primarily due to TMA excretion, which is much the greater.